Surgical ultrasonography at the bedside: a comparison of surgical trainees with trained sonographers for symptomatic cholelithiasis – a first Australian experience. Issue 5 (28th November 2018) - Gaszynski, Rafael; Lim, Christopher; Chan, Daniel L.; Fisher, Oliver M.; Das, Kamala Kanta; Merrett, Neil; Wilson, Robert; Cosman, Peter
Abstract : Background: Symptomatic cholelithiasis accounts for a significant burden of emergency general surgical presentations in Australia and the Western population. Access to hepatobiliary ultrasonography to facilitate diagnosis can lead to delays in timely treatment. Surgical ultrasonography at the bedside (SUB) can mitigate this barrier to patient care. This study assessed the diagnostic accuracy of SUB by trainees versus formal ultrasonographer or computed tomography examination for suspected symptomatic cholelithiasis. Methods: A prospective non‐inferiority study of emergency patient admissions with abdominal pain in two tertiary referral hospitals during July 2017 to October 2018 was performed. Results of SUB were compared with accredited radiographer ultrasonography or computed tomography and histopathological assessment. Positive findings at SUB for symptomatic cholelithiasis included: cholelithiasis, gallbladder wall thickness ˃3 mm, pericholecystic fluid or sonographic Murphy's sign. Results: One hundred patients with epigastric or right upper quadrant pain underwent SUB. Mean patient age was 49 years (range 20–90 years), with 61 females and 39 males. Sensitivity and specificity for diagnosis of symptomatic cholelithiasis was 94.9% and 100% for SUB and 98.7% and 100% for accredited radiographers. Diagnostic accuracy was 96% for SUB and 99% for radiographer ultrasonography. Positive predictive value and negative predictive value were 100% and 84.6% for SUB and 100% and 96% for radiographers. The inter‐rater reliability for features compatible with the diagnosis of symptomatic cholelithiasis was good with a kappa of 0.758 (95% confidence interval 0.587–0.929, P < 0.001). Conclusion: This first Australian experience demonstrates that general surgical trainees can accurately diagnose cholecystitis with SUB and this assessment is not inferior and has substantial agreement with accredited radiographer ultrasonography.